Monetary policy, inequality and political instability. (4th October 2018) - Duarte, Pablo; Schnabl, Gunther
Abstract: Voters in the industrialised countries are increasingly expressing dissatisfaction by dissenting from the established political parties and candidates. Based on the concepts of justice by Hayek, Rawls and Buchanan, we argue that the growing dissatisfaction is rooted in the asymmetric pattern of monetary policies since the mid‐1980s for two reasons. First, the structurally declining interest rates and the unconventional monetary policy measures have granted privileges to specific groups. Second, the increasingly expansionary monetary policies have negative growth effects, which have reduced the scope for compensation of the ones excluded from the privileges. As a result, the acceptance of the prevailing economic and political order is undermined and political instability increases.